2011
DOI: 10.1002/cncr.25989
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of intrahepatic distant recurrence by transcatheter arterial infusion chemotherapy with platinum agents for stage I/II hepatocellular carcinoma

Abstract: BACKGROUND:The effectiveness of additional chemotherapy in preventing intrahepatic distant tumor recurrence of hepatocellular carcinoma (HCC) has not been fully established. The authors compared the efficacy of 2 platinumbased chemotherapeutic agents in combination with radical local treatment for preventing intrahepatic distant recurrence (IDR). METHODS: Seventy-eight patients with stage I/II HCC aged 45 to 85 years underwent transcatheter arterial chemoembolization and/or radiofrequency ablation after they r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…When we investigated the effect of the addition of TAI with DDP-H and carboplatin as pretreatment prior to TACE/radiofrequency ablation therapy as radical local treatment for stage I/II HCC, we reported that whole-liver TAI using DDP-H significantly inhibited intrahepatic recurrence (9). In addition, in patients with JIS 0ā€“1 stage HCC, survival was significantly prolonged in the group that received whole-liver TAI with DDP-H compared with the group that did not undergo infusion, and the results of the multivariate analyses demonstrated that performing whole-liver TAI with DDP-H was a factor contributing to improved survival (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we investigated the effect of the addition of TAI with DDP-H and carboplatin as pretreatment prior to TACE/radiofrequency ablation therapy as radical local treatment for stage I/II HCC, we reported that whole-liver TAI using DDP-H significantly inhibited intrahepatic recurrence (9). In addition, in patients with JIS 0ā€“1 stage HCC, survival was significantly prolonged in the group that received whole-liver TAI with DDP-H compared with the group that did not undergo infusion, and the results of the multivariate analyses demonstrated that performing whole-liver TAI with DDP-H was a factor contributing to improved survival (10).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that whole-liver transcatheter arterial infusion (TAI) with a high concentration of a fine-powder formulation of cisplatin (DDP-H) (IA-call Ā® ; Nippon Kayaku Co. Ltd., Tokyo, Japan) prior to radical local treatment inhibited intrahepatic recurrence of HCC (9), and that whole-liver TAI of DDP-H administered to HCC patients with a Japan Integrated Staging (JIS) score of 0ā€“1 improved survival (10). …”
Section: Introductionmentioning
confidence: 99%
“…While intra-arterial chemotherapy is not highly appreciated in the West, hepatic arterial infusion resulting in high local drug concentrations is expected to improve the prognosis and prevent recurrence, because lesions are often localized to the liver even in the advanced stage of HCC, and various regimens have been attempted without reaching consensus on the administration method or dose level. We evaluated the effectiveness of additional chemotherapy of the platinum-containing drugs carboplatin (CBDCA) and DDP-H in preventing intrahepatic distant tumor recurrence [16]. A total of 78 patients with a diagnosis of primary stage I/II HCC who underwent TACE and RFA after whole liver arterial infusion of CBDCA (25 patients) or DDP-H (53 patients) for local control and recurrence prevention were followed up on a long-term basis, and the clinical background factors, intrahepatic distant tumor recurrence rate, and intrahepatic distant tumor recurrence factors were compared between the CBDCA and DDP-H groups.…”
Section: Significance Of Platinum-containing Drugs In Transhepatic Armentioning
confidence: 99%
“…There is one report that RFA with sequential HAIC using cisplatin contributed to a longer disease-free interval [16]. HAIC using cisplatin before RFA might prevent an increase in the size of pre-existing microscopic tumor foci.…”
Section: Chemotherapeutic Agentsmentioning
confidence: 99%
“…However, in cases in which extrahepatic spread is minimal and local control of liver tumors is considered more important, HAIC is useful and may offer survival benefits, even when there are extrahepatic metastases. HAIC has often been used in these cases in Japan [16,17]. …”
Section: Introductionmentioning
confidence: 99%